2019
DOI: 10.1177/0218492319859806
|View full text |Cite|
|
Sign up to set email alerts
|

Diaphragmatic palsy after cardiac surgery in adult and pediatric patients

Abstract: Background Important differences in the mechanism of respiration between adults and children warrant distinction in the management of diaphragmatic paralysis as a complication of cardiac surgery. We describe the management and outcomes of this complication in both groups. Methods We retrospectively analyzed 16 patients (5 adults and 11 children) with diaphragmatic paralysis after cardiac surgery performed between 2008 and 2018. Clinical examination, chest radiography, and confirmation with fluoroscopy in selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Other contributions to lung dysfunction include alterations of the chest wall's mechanics due to sternotomy, the presence of postoperative atelectasis, pulmonary edema or pleural effusion, and impaired respiratory efforts due to postoperative pain [20,21]. Phrenic nerve injury has also been reported to induce hemidiaphragmatic paresis or paralysis after the surgical correction of CHD, resulting in poor PFT [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Other contributions to lung dysfunction include alterations of the chest wall's mechanics due to sternotomy, the presence of postoperative atelectasis, pulmonary edema or pleural effusion, and impaired respiratory efforts due to postoperative pain [20,21]. Phrenic nerve injury has also been reported to induce hemidiaphragmatic paresis or paralysis after the surgical correction of CHD, resulting in poor PFT [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a retrospective cohort study in the United States between January 1, 2005, and November 30, 2007, showed that the 30-day readmission rate after cardiac surgery ranged from 8.3% to 21.1%, with the most common reasons for readmission being postoperative infection (16.9%) and heart failure (12.8%) (12) . Iribarne and colleagues in a prospective study reported that the overall rate of readmission was 18.7% with female gender, diabetes mellitus, COPD, elevated creatinine, and lower hemoglobin being the top most common risk factors for re-admission after cardiac surgery (13) . Additionally, a recent retrospective observational study done in Northern New England revealed that the 30-day readmission rate after cardiac surgery was 12.3% (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent retrospective observational study done in Northern New England revealed that the 30-day readmission rate after cardiac surgery was 12.3% (14) . Moreover, there is a variation of the most common type of cardiac surgery associated with readmission (13)(14)(15) . Lowering readmission rates is an important goal of all care providers for future quality improvement and cost contaiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-invasive ventilation is a preferred therapy to maintain respiratory function and allow the diaphragmatic function to recover [14]. Other conservative DD management mainly includes spirometry, chest physiotherapy, daily walking, taking frequent deep breaths and keeping a semi-sitting position [47]. One-year inspiratory muscle training after cardiac surgery can improve diaphragmatic mobility and the inspiratory muscle strength of children with DD [ 48 ] .…”
Section: Diaphragmatic Ultrasound In Treatmentmentioning
confidence: 99%